Potential impact of climatic change on medicinal plants used in the Karen women’s health care in Northern Thailand - Kornkanok Tangjitman (2018)
© 2015, Prince of Songkla University. All rights reserved. Global climate change can be expected to drive losses in plant diversity. To exemplifying this issue, the potential impact of climate change on nine medicinal plants relating to Karen women’s healthcare in northern Thailand was investigated using species distribution models. Climatic and non-climatic variables were used to develop the distribution models. The greenhouse gas emissions scenarios, A1B (medium-high emission) and A2 (high emission) were used to examine the potential future species distribution for year 2050 and 2080. It was shown that a combination of climatic and non-climatic factors had strong effects on the distribution of medicinal plant species. Eight plant species were predicted to reduce suitable area in northern Thailand whereas one species is predicted to increase suitable area. Following IUCN Red List criteria, seven of the studied plant species were categorized as critically endangered under A1B or A2 scenarios by 2080. The importance of planning for climate change effects on the availability of wild-collected plant for rural populations was pointed out.